KODE ETIK JURNALISTIK DALAM PRAKTIK FOTOJURNALISME: KASUS KAMPANYE PEMILIHAN PRESIDEN 2009 DI INDONESIA - Yuniar, Ririt (Jurnal Kawistara, 2011)
Journalistic photos appear in newspapers for news purposes. In many cases, many parties are interested in using the mass media for their own vested interests. The photos of the Presidential and Vice-Presidential candidates in the 2009 Indonesian election were examples of such uses. These photos contained symbols which were manipulated and presented in the public sphere. Hence, these photos also reflected power relations within Indonesian society, a society which is full of individual interests. This study attempts to show how the photojournalism appearing in the media during the 2009 election time was intensively used by the candidates, who were also the capital backers. The photos were not presented as they were, but rather composed upon the candidatesâ request for the purposes of image building. For several reasons, including media survival in the global era and its heavy competition and pragmatic motivations, some media have shown a loss of âindependency.â This study also shows that journalistic photos record the existence of values and interests of those appearing on newspaper. The 2009 Presidential and Vice Presidential campaign in Indonesia, one framed in photojournalism, is a social reality analogous to social theatre or a theatrical performance.